2016
DOI: 10.3389/fmicb.2016.01847
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Distribution of Phenol Oxidase Producing Fungi from Soda Lake and Description of Curvularia lonarensis sp. nov.

Abstract: Soda lake is hyper alkaline and saline habitat located in closed craters with high evaporation rate. In current study fungal diversity from water and sediment samples of a soda lake (Lonar lake) located in Buldhana district of Maharashtra, India was investigated using extensive culturomics approach and mimicking the natural conditions of Lonar lake in culture media. A total of 104 diverse isolates of extremophilic fungi were recovered from this study and phylogenetically characterized by internal transcribed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Curvularia species have also been reported from substrates such as air (Almaguer et al 2012, Hargreaves et al 2013), aquatic environments (Verma et al 2013, Su et al 2015, Sharma et al 2016) and soil (Manamgoda et al 2011, Marin-Felix et al 2017a). …”
Section: Introductionmentioning
confidence: 99%
“…Curvularia species have also been reported from substrates such as air (Almaguer et al 2012, Hargreaves et al 2013), aquatic environments (Verma et al 2013, Su et al 2015, Sharma et al 2016) and soil (Manamgoda et al 2011, Marin-Felix et al 2017a). …”
Section: Introductionmentioning
confidence: 99%
“…It is the only crater formed due to the high-velocity meteoritic impact on basaltic rock. Many studies have reported the biodiversity associated with Lonar Soda Lake (Joshi et al, 2007 ; Pathak and Deshmukh, 2012 ; Tambekar and Dhundale, 2012 ; Sharma et al, 2016 ). Microbes isolated from the soda lake region manifest complex microbial food webs interconnecting various biological cycles via redox coupling.…”
Section: Introductionmentioning
confidence: 99%
“…N fertilization has the potential to promote soil organic carbon (SOC) sequestration (Jian et al, 2016), although some studies show a negative or no effect of N fertilization on SOC sequestration (Aref & Wander, 1997; Brown et al, 2014; Khan et al, 2007). The contrasting effects of N fertilization on SOC stock partly lie in the differential responses of mineralization of slow turnover SOC fractions (e.g., lignin or litterfall; Dou et al, 2016), which are depolymerized by extracellular oxidative enzymes (oxidases) excreted by soil bacteria and fungi (Gallo et al, 2004; Sharma et al, 2016). As either plant inputs or indigenous SOC are chemically recalcitrant (Trumbore, 2000) and must be processed via microbial decomposition and oxidative catalyzation, the net changes of plant inputs and decomposition loss, that is, SOC accumulation, are likely represented by the dynamics of oxidases.…”
Section: Introductionmentioning
confidence: 99%